2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24127
|View full text |Cite
|
Sign up to set email alerts
|

Formative vs. Summative ABET Assessment: A Comprehensive Graphic Representation for a New BME Program

Abstract: This paper presents an innovative methodology for the assessment of a new Biomedical Engineering (BME) program. Biomedical engineering programs are quite new in the engineering educational system. To date, in the state of Pennsylvania there are only six programs that have been accredited by ABET out of the 91 programs accredited nationwide 1 . While the guidelines of ABET are quite general and applicable to a variety of programs with different focuses, the scarcity of published data on BME specific programs po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The artifacts aligned with each outcome were designed specifically to satisfy each dimension of the rubric. Once aligned, these artifacts were evaluated in Blackboard Outcomes using an established four‐point rubric for each outcome and dimension (Piovesan and Vernaza 2015; Schmitz, Vernaza, and Piovesan 2016). The specific outcomes assessed, excerpted from a larger list of outcomes, were: B: An ability to design and conduct experiments as well as to analyze and interpret data D: An ability to function on multidisciplinary teams K: An ability to use techniques, skills, and modern engineering tools necessary for engineering practice L: An ability to apply in‐depth knowledge of biology M: An ability to apply knowledge of statistics …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artifacts aligned with each outcome were designed specifically to satisfy each dimension of the rubric. Once aligned, these artifacts were evaluated in Blackboard Outcomes using an established four‐point rubric for each outcome and dimension (Piovesan and Vernaza 2015; Schmitz, Vernaza, and Piovesan 2016). The specific outcomes assessed, excerpted from a larger list of outcomes, were: B: An ability to design and conduct experiments as well as to analyze and interpret data D: An ability to function on multidisciplinary teams K: An ability to use techniques, skills, and modern engineering tools necessary for engineering practice L: An ability to apply in‐depth knowledge of biology M: An ability to apply knowledge of statistics …”
Section: Methodsmentioning
confidence: 99%
“…The raw data was exported from Blackboard Outcomes and processed using custom Matlab code (Matlab R2016a, MathWorks, Natick, MA) to create a radial plot of the scores (Piovesan and Vernaza 2015). Any scores lower than 3 were addressed through changes in the course.…”
Section: Methodsmentioning
confidence: 99%
“…Formative and summative assessment approaches are also extensively used for program assessment for ABET accreditation. A study on formative versus summative assessment for a Biomedical Engineering (BME) program concluded that most of the ABET outcomes were achieved at marginal levels by the formative assessment [4]. A good assessment process at the course level includes having Course Learning Objectives and tie them to Program Learning Objectives.…”
Section: Introductionmentioning
confidence: 99%